IMPLEMENTASI MARKETING PUBLIC RELATIONS NITYA AESTHETIC CLINIC DALAM MEMBANGUN BRAND IMAGE SEBAGAI KLINIK KECANTIKAN PREMIUM - Mike Indarsih; Horidatul Bakiyah; Fajar Diah Astuti; Afdaliza; Siti Alpiah; Puput Martanto (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study analyzes the marketing public relations strategy of Nitya Aesthetic Clinic in building its brand image as a premium beauty clinic in Citra Raya, Tangerang. The growing demand for high-quality aesthetic services in suburban areas requires effective communication strategies to remain competitive. This research employs a qualitative approach using a case study method and a constructivist paradigm. Data were collected through in-depth interviews, direct observations, and documentation. The theoretical framework is based on Thomas L. Harris’s marketing public relations concept, which includes push, pull, and pass strategies. The findings reveal that Nitya Aesthetic Clinic integrates all three strategies: push through direct promotions such as events and exhibitions, pull through educational content, storytelling, and the use of digital media, and pass through collaborations with influencers and KOL (key opinion leaders) that reinforce its premium image. Internal factors such as consistent SOP-based services, staff training, and regular evaluations further strengthen the brand image. The synergy between external communication strategies and high-standard internal services effectively positions Nitya Aesthetic Clinic as a trusted and competitive premium beauty clinic within the rapidly growing aesthetic industry. Keywords: Marketing Public Relations, Brand Image